The Influence of Assets, Credit Guarantees, and Interest Rates on Customer Credit Decisions - Cherly Elisabeth (Manunggal Halim Jaya, 2023)
This research was conducted to analyze Assets, Credit Guarantees, and Interest Rates on Customer Credit Decisions at Bank SULSLBAR Majene Branch. This study uses a type of quantitative research, quantitative methods are all data expressed in the form of numbers. Data collection was carried out through a questionnaire with a quantitative approach. The sampling technique in this study was simple random sampling with a total of 100 respondents and using multiple regression analysis. The results of the study show that partially assets have a positive and significant effect on customer credit decisions, as evidenced by the t count value which is greater than t table, namely 2.337 > 1.984 and a significance level smaller than 0.05, namely 0.021. The credit guarantee variable partially also has a positive and significant effect on customer credit decisions, as evidenced by the t-value which is greater than t-table, namely 1.999>1.984 and a significance level that is less than 0.05, namely 0.048. The interest rate variable partially has a positive and significant effect on customer credit decisions, as evidenced by the t-value which is greater than t-table, namely 3.648 > 1.984 and a significance level that is smaller than 0.05, namely 0.000. Assets, credit guarantees, and interest rates simultaneously have a positive and significant effect on customer credit decisions, as evidenced by the calculated f value, which is greater than f table, namely 37.074 > 2.92.